2013
DOI: 10.1017/s0029665113003790
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating dietary PUFA in animal feed: implications for human health

Abstract: Milk, meat and eggs tend not to be regarded as an important source of PUFA. They are disproportionally high in SFA compared with their PUFA content, especially those from cattle and sheep, since their rumen microbes are responsible for the loss of over 90 % of PUFA intake by livestock. This need not necessarily be the case since the relative proportion of PUFA in these foods is dictated by livestock management, especially feeding, and this can be manipulated to boost their content of crucial long-chain n-3 fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…During almost all of the nutrition transitions worldwide (with South Korea being an exception [19]) an increase in energy from plant based fats has occurred, resulting in an increase in dietary LA [13]. Furthermore, due to changes in animal feed practices resulting in an increase in grain feeding, animal products now also have an increased LA content than their traditional counterparts [20,21]. A key follow-on from these nutrition transitions has been an increase in obesity rates and the prevalence of non-communicable diseases such as CVD and type 2 diabetes mellitus (T2DM) [22].…”
mentioning
confidence: 99%
“…During almost all of the nutrition transitions worldwide (with South Korea being an exception [19]) an increase in energy from plant based fats has occurred, resulting in an increase in dietary LA [13]. Furthermore, due to changes in animal feed practices resulting in an increase in grain feeding, animal products now also have an increased LA content than their traditional counterparts [20,21]. A key follow-on from these nutrition transitions has been an increase in obesity rates and the prevalence of non-communicable diseases such as CVD and type 2 diabetes mellitus (T2DM) [22].…”
mentioning
confidence: 99%
“…Butler 2014;Vazirigohar et al 2014) present opportunities to improve final product quality including increases in conjugated linoleic acid, omega-3 fatty acids, minerals in animal products, and product shelf life through manipulation of animal feeding. Many of these changes elicit positive effects on human health (Ip et al 1991;Belury 2002;Bauman et al 2006).…”
Section: Animal Nutrition and Product Qualitymentioning
confidence: 99%
“…44 On the other hand, several studies have demonstrated the potential benefits of n-3 PUFA supplementation for health. 29,[43][44][45] Amino acids, peptides, nucleotides and sugars correspond to meat polar metabolites and, many of them are water-soluble precursors of meat flavour. [51][52][53][54] The presence of nucleotides in meat is important not only for the flavour but also because some nucleotides are considered biomarkers for relevant metabolic pathways.…”
Section: Redox Processes In Meatmentioning
confidence: 99%
“…27,29,30,44,47,80,102 Together with the increasing demand for high quality meat, there is an increasing public concern to propose a more humane production of meat, and for alternatives to prevent environmental impact due to intensive livestock farming. Diet manipulation has the advantages to naturally induce changes in the meat composition avoiding the use of antibiotics and hormones.…”
Section: Nutritional Strategies For Improving Meat Qualitymentioning
confidence: 99%
See 1 more Smart Citation